2020
DOI: 10.1002/anie.201915084
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalysed Radical Polymerisation by Living Bacteria

Abstract: The ability to harness cellular redox processes for abiotic synthesis might allow the preparation of engineered hybrid living systems. Towards this goal we describe a new bacteria‐mediated iron‐catalysed reversible deactivation radical polymerisation (RDRP), with a range of metal‐chelating agents and monomers that can be used under ambient conditions with a bacterial redox initiation step to generate polymers. Cupriavidus metallidurans, Escherichia coli, and Clostridium sporogenes species were chosen for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 56 publications
0
50
0
Order By: Relevance
“…Intriguingly, in the field of polymer chemistry, it has been recently reported that radical polymerization can be performed by utilizing microbial EET. [73][74][75] For example, Magennis et al utilized Escherichia coli (E. coli) and Pseudomonas aeruginosa to regenerate Cu(I), a catalyst for the polymerization, to synthesize microbe-templated polymers. [73] They demonstrated that the polymers selectively bind to the microbial strain that utilized as the template.…”
Section: General Features Of Type I Mediatorsmentioning
confidence: 99%
“…Intriguingly, in the field of polymer chemistry, it has been recently reported that radical polymerization can be performed by utilizing microbial EET. [73][74][75] For example, Magennis et al utilized Escherichia coli (E. coli) and Pseudomonas aeruginosa to regenerate Cu(I), a catalyst for the polymerization, to synthesize microbe-templated polymers. [73] They demonstrated that the polymers selectively bind to the microbial strain that utilized as the template.…”
Section: General Features Of Type I Mediatorsmentioning
confidence: 99%
“…Minimal polymerisation was observed in the absence of live cells, indicating the importance of cellular metabolism to the catalytic cycle to regenerate active Fe(II). 17 It is noteworthy that polymerisation was also observed with the Gram-positive anaerobe Clostridium sporogenes, however only 34% conversion was achieved in comparison to 61% and 78% for C. metallidurans and E. coli, respectively. This was hypothesised to be due to C. sporogenes being less efficient at reducing Fe(III) than Gram-negative strains.…”
Section: Microbe Mediated Polymerisationmentioning
confidence: 96%
“…16 Radical polymerisation has also been demonstrated using the metal-reducing Gram-negative bacterium Cupriavidus metallidurans and the model laboratory bacterium Escherichia coli. 17 Native membrane reductases in both organisms were able to reduce Fe(III) to Fe(II) to activate a series of radical initiators for ATRP. Minimal polymerisation was observed in the absence of live cells, indicating the importance of cellular metabolism to the catalytic cycle to regenerate active Fe(II).…”
Section: Microbe Mediated Polymerisationmentioning
confidence: 99%
“…[67] It has been demonstrated that in situ polymerization in biological systems can be achieved using thermal initiation and enzymatic approaches. [68][69][70] As an alternative methodology, photopolymerization offers a key advantage in spatio-temporal control, allowing for external manipulation of these strategies. [71,72] Moving beyond encapsulating cells within a matrix, directing polymerization onto key components of a cell provides a unique opportunity to modulate cell properties using synthetic materials.…”
Section: Photopolymerizationmentioning
confidence: 99%